PENGARUH INFLASI DAN SUKU BUNGA TERHADAP INDEKS HARGA SAHAM GABUNGAN TAHUN 2010-2012 - Koapaha, Hartini Pop (JBE (Journal of Business and Economics); Volume 12 No.1, 2013 JBE UNKLAB, 2013)
The aim of this research is to analyze the impact of macroeconomics factors (inflation and BI rate) toward  Indeks Harga Saham Gabungan (IHSG).  Therefore, this research has constructed two research questions and two hypotheses. The method used in this research are simple linear regression model to analyze the impact of the inflation and BI rate to the price index of IHSG. The result of this research show that the inflation has significant influence toward IHSG. While the BI rate does not affect IHSG significantly.